ANALISIS BIMBINGAN BAGI ANAK BERPRILAH BERMASALAH DI SD GMIT 33 MORU 01 - Novita Yuliana Wabang; Mince Illu, Ria Bolang, Petrus Mau Tellu Dony, Yessy Mata, Triznawasti Yuditha Daik (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to describe and analyze the effectiveness of guidance services in addressing problematic behavior in children with problematic behavior at Gmit 33 Moru 01 Elementary School, Abad District, Alor Regency. The problematic behaviors in question include aggressiveness, rejection of rules, impoliteness, and difficulties in social interaction. The research approach used was a qualitative case study method. The subjects were three fourth-grade students exhibiting problematic behavior at an elementary school. Data were collected through observation, interviews with teachers and parents, and documentation. The results showed that providing individual and group guidance services, involving play counseling techniques, group discussions, and positive reinforcement, can help reduce the intensity of problematic behavior. Consistent guidance and collaboration between teachers, counselors, and parents proved to be key factors in the success of the intervention. This study recommends increasing teachers' capacity to understand and address problematic behavior through appropriate guidance approaches. Problematic behavior in children is a common challenge faced by teachers, parents, and guidance personnel in educational and social settings. Problematic behavior can take the form of aggression, refusal to follow rules, antisocial behavior, or emotional disturbances, which can impact a child's social, academic, and psychological development. Appropriate guidance is an effective intervention to help children understand and manage these behaviors. This study aims to examine the role and methods of guidance in addressing problematic behavior in children